Edible Tagetes patula Flower and Its Flavanoid Patuletin: Pre-clinical Evidence of Selective Systemic Toxicity - Muhammad Kashif; Hazar Khan; Asma Khawer; Hafiz Syed Imran ul Haq; Muhammad Aitmaud Uddolah Khan; Mudassar Azhar; Shaheen Faizi; Ahsana Dar Farooq (International Journal of Medical Toxicology and Forensic Medicine)
Background: Phytotherapy is a common practice around the world, including Pakistan. One such medicinal plant is Tagetes patula. Its flower is edible and used for various local illnesses, especially cancer. However, they lack the toxicological evaluation of this plant, including its active flavonoid i.e. Patuletin, which is addressed in the present investigation. Methods: Wistar rats of either sex (150 g) were intraperitoneally treated (acute [1 day], sub-acute [7 days], and repeated dose [28 days]) with T. patula flower methanolic extract (1 and 2 g/kg) and patuletin (5, 30 and 60 mg/kg). Weight changes in rats were observed. Additionally, the hematological and biochemical (hepatic and renal function) indicators were assessed using respective analyzers. Histological examination of the liver and kidney was also performed following hematoxylin and eosin staining. Results: Our data showed that none of the treatments caused a significant alteration in the weight of rats compared to the control. Among the various hematological parameters, the white blood cell count was significantly reduced by both extract and patuletin treatments. However, the enhanced levels of aspartate aminotransferase along with morphological changes in the liver were observed only in patuletin-exposed animals. Conclusion: The present study demonstrated the toxic potential of T. patula flower methanolic extract and its active flavonoid i.e. patuletin. It further recommends the implementation of a regulatory check over its consumption to protect fellow citizens from the harmful effects.